Heuristic Based Low Volatility Portfolio For Retail Investors In Malaysian Stock Market - Siti Masitah Elias,; Muhd Faiz Najmi Abdul Wahab,; Asmah Mohd Jaapar; Karmila Hanim Kamil (HRMARS, 2024)
Indexed by ERA